Major Power Relations in a Post-Pandemic World Order - Jiemian Yang (China Quarterly of International Strategic Studies, 2020)
The still raging Covid-19 pandemic has brought sweeping and profound changes to the world. Having claimed more than one million lives and sickened many times more, the novel coronavirus has plunged the global economy into a deep recession, exacerbated existing political divisions, and changed the conception of human security. The global pandemic has not so much changed the basic direction of world history as accelerated the pace of it. The mega-trend toward greater equality and justice in global power distribution is unstoppable. At this moment of reordering, major powers need to assume the special responsibility for upgrading and updating the principles, concepts, and institutions for a new world order. Major obstacles to a smooth transition to a new order include the U.S. policy shift to unilateralism, protectionism, and nationalism on President Trump’s watch, the evolving coronavirus pandemic and its long-lasting aftershocks, emerging powers’ lack of strategic capability and/or political will to play a larger role, and glaring gaps between the mandates and means of international organizations. Just as it will take a coordinated global response to vanquish the virus, it will take complementary rather than confrontational policies of major powers to ensure a peaceful transition to a new world order.